The perceptions of the youth generation regarding the 'Buya Hamka' movie - Guntur Bayu Taufiqqurahman; Dani Fadillah; Wiwiek Afifah (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2023)
This study endeavors to assess and determine the perceptions of the Muhammadiyah youth cohort in the specified Yogyakarta region regarding the movie